Tsunami of India’s Second COVID-19 Wave: B.1.617 and Black Fungus (Asian Journal of Pharmaceutics (AJP), 2022)
The catastrophic second wave of COVID-19 caused over 26 million cases in India making it the epicenter ofthe global pandemic. The sudden surge in COVID-19 infections is intertwined with various variants includingB.1.617. Globally, health authorities have expressed major concerns that key mutations L452R and E484Q locatedat the receptor-binding domain of the spike protein would have additive effects on SARS-CoV-2 evasion from thevaccine-elicited antibodies. As India struggles with COVID-19 cases spiraling out of control, it is simultaneouslycaught by escalating cases of “Black Fungus.” Researchers are hurrying to determine the many circulatingvariants and to know the unknowns about biology and pathology of the mutating SARS-CoV-2 to analyze thethreat possessed by them.